Increasing Natural Resistance Associated Macrophage Protein 1 serum level after Miana treatment in BALB/c induced Klebsiella pneumoniae experimental research. (May 2021) - Wahyuni, Titis Dewi; Hatta, Mochammad; Bukhari, Agussalim; Santoso, Arif; Massi, Muhammad Nasrum
Abstract: Background: Miana ( Coleus Scutellariodes [L] Benth) inhibits growth of bacterial pathogen inside macrophage. Objective: The aim of this study is to determine the protein level of Natural Resistance Associated Macrophage Protein 1 (NRAMP1), after administration of Miana extracts in BALB/c mice induced Klebsiella pneumoniae . Methods: This is an experimental study using animal model with post test-only controlled group design. Twenty healthy adult male BALB/c mice were randomly divided into four groups, negative control group (distilled water), Levofloxacin 100 mg/kg, injection intraperitoneal, first treatment group (Miana leaves extract/MLE 510 mg/kg) and second treatment group (Miana + levofloxacin). MLE were administered via gastric gavage for ten consecutive days. The blood was drawn from each mice on the first day, on the eight day of experiment (2 h after treatment), and at 10 days. The blood sample was examined by ELISA to determine the NRAMP1 protein level. Analysis of the number of lung tissue bacteria used Plate count agar to see the growth of Klebsiella pneumonia . Results: NRAMP1 protein level in BALB/c mice after administration of Miana extract was increased significantly in after 10 days treatment (p < 0.0001). The highest increasing in protein levels was found in treatment group (Miana + levofloxacin) with an increase before treatment 3036, 07 to 10010, 30 pg/ml after treatment p < 0, 0001. Conclusion: NRAMP1 protein level in BALB/c mice were highest increasing in protein levels after administration of Miana extract and Levofloxacin compared Miana or Levofloxacin only and clinical impact proved a comparable effect on suppressing Klebsiella pneumoniae growth. The institutional protocol number of this study is 1010/UN4.6.4.5.31/PP36/2019. Highlights: NRAMP1 was increased significantly in after 10 days treatment of Miana ( Coleus scutellaroides (L) Benth ). NRAMP1 protein level in were highest increasing after administration of Miana and Levofloxacin compared Miana or Levofloxacin only. The administration of Levofloxacin and Miana proved a comparable effect on suppressing Klebsiella pneumoniae growth. Further study needed to explore in the mRNA expression of NRAMP1 gene after administration of Levofloxacin and Miana.